2001
DOI: 10.1111/j.1479-828x.2001.tb01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion rate associated with hysterectomy for benign disease

Abstract: The transfusion rate associated with hysterectomy for benign disease is an indirect indicator of haemorrhage. It is used in quality assurance activities and is one measure of standard of care. This retrospective study was conducted to determine the transfusion rate for these operations in a tertiary referral hospital. In addition, it was considered that the information could be used in deciding the need for a routine preoperative group and save policy (G and S). The Blood Bank records of all women undergoing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
3
7
1
Order By: Relevance
“…Consistent with previous studies, we found a significantly higher transfusion rate for abdominal hysterectomy compared with vaginal hysterectomy (7 vs. 3%) (1,14). However, for both of these surgical procedures the transfusion rates in our study were higher than previously reported rates with respect to studies published after 1990 (1,9,15–17), where the reported transfusion rates were 0.38–2.4% at vaginal hysterectomy and 2.18–4.7% for abdominal hysterectomy. This discrepancy may be explained by differences in study design but may also reflect the presence of a generally high transfusion rate in Denmark, with a possible overuse of blood components often claimed to be caused by a very liberal transfusion policy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies, we found a significantly higher transfusion rate for abdominal hysterectomy compared with vaginal hysterectomy (7 vs. 3%) (1,14). However, for both of these surgical procedures the transfusion rates in our study were higher than previously reported rates with respect to studies published after 1990 (1,9,15–17), where the reported transfusion rates were 0.38–2.4% at vaginal hysterectomy and 2.18–4.7% for abdominal hysterectomy. This discrepancy may be explained by differences in study design but may also reflect the presence of a generally high transfusion rate in Denmark, with a possible overuse of blood components often claimed to be caused by a very liberal transfusion policy.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, even when sensitization of transfused red blood cells by antibody is demonstrated in the laboratory, clinical hemolysis is not always present, and even when changes in biochemical parameters indicate the presence of hemolysis, it is not always associated with increased morbidity. Taken together, our data support other studies suggesting that the clinical impact of the preoperative routine ‘type and screen’, with or without a computer cross‐match procedure, is questionable for surgical procedures associated with a very low transfusion rate (1,9,20).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, more than 1 in 10 patients undergoing hysterectomy required a transfusion. This finding contrasts with previous reports where transfusions ranged between 2.2% [7] and 5% [8] of gynecologic surgeries. A fact that must be considered is that the study hospital is a teaching hospital, and resident physicians who were training in obstetrics and gynecology performed many of the hysterectomies; however, a professor was always present and provided support during surgery if necessary.…”
Section: Discussioncontrasting
confidence: 99%
“…In 1990 Brunello 17 documented a series of 62 vaginal hysterectomies. In 2001, Varol 18 published a retrospective analysis of 462 vaginal hysterectomies and Otton 19 published a paper detailing transfusion rates in association with 532 vaginal hysterectomies. Thus there are little sizable and/or contemporary Australian data of adverse outcomes associated with vaginal hysterectomy available.…”
Section: Introductionmentioning
confidence: 99%